Internet-based basic body awareness therapy in fibromyalgia syndrome: A report of three cases - ERSÖZ HÜSEYİNSİNOĞLU, BURCU; YOLCU, GÜNAY; KARADAĞ SAYGI, NAİME EVRİM (My University, 2023)
Previous literature has shown that basic body awareness therapy (BBAT) may be an effective treatment for fibromyalgia syndrome (FMS). This study constitutes the first case study evaluating internet-based BBAT for FMS. The purpose of this case study was to describe the feasibility and preliminary outcomes of an internet-based BBAT training for a total of 8 weeks in three patients with FMS. The patients underwent a synchronous individual internet-based BBAT training. Outcomes were assessed using Fibromyalgia Impact Questionnaire Revised, Awareness-Body-Chart, Short-Form McGill Pain Questionnaire (SF-MPQ), and plasma fibrinogen level. These measures were administered at baseline and after the treatment. Patient satisfaction with the treatment was evaluated using a structured questionnaire. At the post-treatment evaluation, each patient showed improvements in all outcome measures. All patients had clinically significant changes in Fibromyalgia Impact Questionnaire Revised. The SF-MPQ total score in Patients 1 and 3 exceeded the minimal clinically important difference. All patients\" pain severity exceeded the minimal clinically important difference for Visual Analogue Scale (SF-MPQ). Besides, we found some benefits in body awareness and the level of dysautonomia. At the end of the treatment, patient satisfaction with the programme was very high. Based on this case study, the application of internet-based BBAT seems feasible and promising for clinical benefits.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Fibromyalgia; telerehabilitation; exercise; case report; MCGILL-PAIN-QUESTIONNAIRE; TURKISH VERSION; RELIABILITY; INTERVENTIONS; VALIDITY